In Vitro and In Vivo Applications of Magnesium-Enriched Biomaterials for Vascularized Osteogenesis in Bone Tissue Engineering: A Review of Literature - Hu, Jie; Shao, Jiahui; Huang, Gan; Zhang, Jieyuan; Pan, Shuting (Journal of functional biomaterials, 2023)
Bone is a highly vascularized tissue, and the ability of magnesium (Mg) to promote osteogenesis and angiogenesis has been widely studied. The aim of bone tissue engineering is to repair bone tissue defects and restore its normal function. Various Mg-enriched materials that can promote angiogenesis and osteogenesis have been made. Here, we introduce several types of orthopedic clinical uses of Mg; recent advances in the study of metal materials releasing Mg ions (pure Mg, Mg alloy, coated Mg, Mg-rich composite, ceramic, and hydrogel) are reviewed. Most studies suggest that Mg can enhance vascularized osteogenesis in bone defect areas. Additionally, we summarized some research on the mechanisms related to vascularized osteogenesis. In addition, the experimental strategies for the research of Mg-enriched materials in the future are put forward, in which clarifying the specific mechanism of promoting angiogenesis is the crux.